ANALYSIS OF FINANCIAL PERFORMANCE USING ECONOMIC VALUE ADDED (EVA) AND MARKET VALUE ADDED (MVA) APPROACH OF STATE-OWNED BANKS (BUMN) LISTED ON INDONESIA STOCK EXCHANGE - Adhitama, Satria; Abdul Muis, Muhammad (Dinasti International Journal of Management Science, 2021)
This study aims to analyze financial performance using Economic Value Added (EVA) and Market Value Added (MVA) approaches of state owned Banks (BUMN) listed on Indonesia Stock Exchange. The research methodology used qualitative descriptive research. The objects of this study are the state owned Banks (BUMN) listed on Indonesia Stock Exchange 2016-2018. The data collection techniques used are secondary data and panel data. The analysis techniques used are by calculating Economic Value Added (EVA) and Market Value Added (MVA). The results of this study indicate that the financial performance of the state owned Banks (BUMN) listed on Indonesia Stock Exchange 2016-2018 in terms of Economic Value Added (EVA) has good financial performance because the Economic Value Added value always more than zero (EVA> 0). In terms of Market Value Added (MVA), in 2016 Bank BNI had negative MVA value (MVA <0) then in 2017 and 2018.BNI Bank had positive MVA value (MVA> 0). BRI and Mandiri Bank had positive MVA value (MVA> 0) in 2016-2018. BTN Bank in 2016-2018 had negative MVA (MVA <0).